America the beautiful and violent : black youth & neighborhood trauma in Chicago - Voisin, Dexter R. (Columbia University Press, 2019)
Dexter R. Voisin provides a compelling and social-justice-oriented analysis of current trends in neighborhood violence in light of the historical and structural factors that have reproduced entrenched patterns of racial and economic inequality. He features the powerful voices and insights of black youth in Chicago and their parents and communities